2011
DOI: 10.1039/c1mb05105a
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic footprinting of the anaerobic bacterium Fusobacterium varium using 1H NMR spectroscopy

Abstract: Metabolic footprinting of the anaerobic bacterium Fusobacterium varium demonstrated the accumulation of six carboxylic acids as metabolic end-products and revealed specific growth requirements and utilization capabilities towards amino acids. Guided by (1)H NMR determinations of residual amino acids in spent medium, a modified chemically defined minimal medium (CDMM*) was developed by minimizing the amino acid composition while satisfying nutritional requirements to support abundant growth of F. varium. Quanti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
8
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 50 publications
1
8
0
Order By: Relevance
“…Such shifts toward increased lactate formation in the presence of nonlimiting concentrations of glucose have also been described for chemostat cultures of Klebsiella aerogenes (70) and several Streptococcus spp. (71,72) and are in agreement with the production of lactate by Fusobacterium varium grown at high glucose concentrations (73). In conventional cockroaches, the accumulation of lactate was less pronounced, which suggested that the normal gut microbiota, like that of termites, comprises active lactate-consuming populations (12).…”
Section: Discussionsupporting
confidence: 68%
“…Such shifts toward increased lactate formation in the presence of nonlimiting concentrations of glucose have also been described for chemostat cultures of Klebsiella aerogenes (70) and several Streptococcus spp. (71,72) and are in agreement with the production of lactate by Fusobacterium varium grown at high glucose concentrations (73). In conventional cockroaches, the accumulation of lactate was less pronounced, which suggested that the normal gut microbiota, like that of termites, comprises active lactate-consuming populations (12).…”
Section: Discussionsupporting
confidence: 68%
“…Altered colonic pH could affect metabolic activity, absorption of short-chain fatty acids (SCFA), and composition of gut microflora and mucosal cell proliferation [34]. Walker et al observed that even a single unit change in pH affected the host microbial community composition as well as production of SCFA, especially among butyrate-producing species [35], a group within which Fusobacterium is included [36][39]. While most bile acids aid solubilization of lipids and facilitate nutrient absorption, some are transformed by intestinal bacteria into toxic secondary bile acids in the colon [40].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the faecal samples from dogs fed the greaves-meal diet had a high preponderance of Fusobacteriales bacteria [32]: an order of bacteria that has been suspected to play a pathogenic role in human intestinal inflammation [34-36]. Therefore, one could hypothesize that Fusobacteria could produce branched VFAs and valeric acid from protein break-down products [53]. Moreover, some Fusobacteria could act as pathogens, which may cause intestinal inflammation that would result in increased faecal calprotectin levels.…”
Section: Discussionmentioning
confidence: 99%